2009
DOI: 10.1016/j.tcm.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Cell Connection to Cardiac Disease

Abstract: Intercalated disks (ICDs) are highly organized cell-cell adhesion structures, which connect cardiomyocytes to one another. They are composed of three major complexes: desmosomes, fascia adherens, and gap junctions. Desmosomes and fascia adherens junction are necessary for mechanically coupling and reinforcing cardiomyocytes, whereas gap junctions are essential for rapid electrical transmission between cells. Because human genetics and mouse models have revealed that mutations and/or deficiencies in various ICD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
134
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(140 citation statements)
references
References 76 publications
2
134
0
4
Order By: Relevance
“…Fascia adherens junctions and desmosomes are essential for the mechanical coupling of myocardial cells. Fascia adherens junctions provide anchorage for actin filaments, and desmosomes provide anchorage for IFs (Sheikh et al, 2009). ROCK2 phosphorylates ERM family proteins, which are cross-linkers of the plasma membrane and actin filaments, and recruits ERM family proteins to plasma membranes (Fukata et al, 1998;Matsui et al, 1998).…”
Section: Cell-cell Adhesion Sitesmentioning
confidence: 99%
“…Fascia adherens junctions and desmosomes are essential for the mechanical coupling of myocardial cells. Fascia adherens junctions provide anchorage for actin filaments, and desmosomes provide anchorage for IFs (Sheikh et al, 2009). ROCK2 phosphorylates ERM family proteins, which are cross-linkers of the plasma membrane and actin filaments, and recruits ERM family proteins to plasma membranes (Fukata et al, 1998;Matsui et al, 1998).…”
Section: Cell-cell Adhesion Sitesmentioning
confidence: 99%
“…Cardiac myocyte-to-myocyte adhesion is maintained by desmosomes, adherens junctions and gap junctions, which together comprise the intercalated disc 5 7. The desmosomes have a complex structure that includes adhesion molecules of the cadherin (desmoglein-DSG and desmocollin-DSC), plakin (desmoplakin-DSP) and catenin (plakophilin-PKP and plakoglobin-JUP) families, which link intermediate filaments of the cytoskeleton to the desmosomal cadherins 8 9.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of evidence comes from studies performed on patients harboring the cardiac muscle disease, arrhythmogenic right ventricular cardiomyopathy (ARVC), which is primarily thought to be caused by pathogenic mutations/defects in genes of the desmosomal cell-cell junction (Sheikh et al, 2009); however, studies have also revealed that patients harboring gap junction mutations also present with specific electrophysiological abnormalities linked to the CCS.…”
Section: Ccs Defects Found In Human Patients With Underlying Defementioning
confidence: 99%